2017
DOI: 10.1186/s12877-017-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-reported health among the elderly in Ghana: a cross sectional study

Abstract: BackgroundSelf-reported health is a widely used measure of health status across individuals. As the ageing population increases, the health of the elderly also becomes of growing concern. The elderly go through life facing social, economic and financial hardships. These hardships are known to affect the health status of people as they age. The purpose of this study is to assess social and health related factors of self-reported health among the elderly in Ghana.MethodsA multivariate regression analysis in form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 92 publications
10
46
1
1
Order By: Relevance
“…In decomposing the concentration index, we found that health inequality was experienced most among those aged 70 years and above, single respondents, those with poor income status, referred to as the poor, and elderly persons with chronic conditions. Our findings are in concordance with other studies that have shown that poor health is often experienced by the least advantaged in the society (Fernandez-Martinez et al 2012;Sözmen et al 2012;Fonta et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In decomposing the concentration index, we found that health inequality was experienced most among those aged 70 years and above, single respondents, those with poor income status, referred to as the poor, and elderly persons with chronic conditions. Our findings are in concordance with other studies that have shown that poor health is often experienced by the least advantaged in the society (Fernandez-Martinez et al 2012;Sözmen et al 2012;Fonta et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Consumption of tobacco, fruit intake, chronic NCDs, engagement in physical activity and vegetable consumption were dichotomised following Gyasi [26]. Self-rated health was dichotomised following Subramanian et al [27], Fonta et al [28] and Bourne [29]. A comprehensive explanation of the evaluation procedure of the dichotomous variables has been reported elsewhere [25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…This subjective health assessment is a valid health status indicator for evaluating an individual's current state of health (Ichoku et al, 2011;Mora et al, 2008). SRH, despite being a self-reported indicator, is often accompanied with bodily sensations and symptoms that are related to disease pathology, and has been shown to predict mortality (Benyamini, 2011;Fonta et al, 2017;GuimarĂŁes et al, 2012).…”
Section: Fear Of Covid-19 and Perceived Physical Healthmentioning
confidence: 99%